2018
DOI: 10.1007/s00355-018-1113-9
|View full text |Cite
|
Sign up to set email alerts
|

The socially acceptable scoring rule

Abstract: We say that an alternative is socially acceptable if the number of individuals that rank it among their most preferred half of the alternatives is at least as large as the number of individuals that rank it among the least preferred half. We show that there exists a unique scoring rule that always selects a subset of socially acceptable alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Note that Mahajne and Volij (2018) introduced a scoring rule, called the half accepted-half rejected (HAHR), which always selects a socially acceptable candidate (and never selects a socially unacceptable candidate). HAHR assigns 1 point to the candidates placed above the line, −1 point to candidates below the line, and a score of 0 to the candidate (if there is one) on the line.…”
Section: Negative Plurality With Runoff (Nprr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that Mahajne and Volij (2018) introduced a scoring rule, called the half accepted-half rejected (HAHR), which always selects a socially acceptable candidate (and never selects a socially unacceptable candidate). HAHR assigns 1 point to the candidates placed above the line, −1 point to candidates below the line, and a score of 0 to the candidate (if there is one) on the line.…”
Section: Negative Plurality With Runoff (Nprr)mentioning
confidence: 99%
“…Assuming that voters have strict rankings (without indifference) on all running candidates, Mahajne and Volij (2018) introduce the concept of a socially acceptable candidate, which is a candidate whom at least half of the voters rank higher than at least half of the candidates in their rankings. They show that there always exists at least one socially acceptable candidate for every preference profile; however, such a candidate may not be elected under some scoring rules, with the exception of a new scoring rule, the half accepted-half rejected (HAHR) rule.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for a certain consensus around a candidate, Mahajne and Volij (2018) have introduced the concept of social acceptability. They say that a candidate is socially acceptable if the number of voters who rank him among their most preferred half of the candidates is at least as large as the number of voters who rank him among the least preferred half.…”
Section: Social (Un)acceptabilitymentioning
confidence: 99%
“…Mahajne and Volij [6] showed that every preference profile has a socially acceptable alternative. The next example shows that a Condorcet winner may not be socially acceptable.…”
Section: Definitionsmentioning
confidence: 99%